5-HT7 receptor-mediated fear conditioning and possible involvement of extracellular signal-regulated kinase. (18th January 2017) - Takeda, Kotaro; Tsuji, Minoru; Miyagawa, Kazuya; Takeda, Hiroshi
Highlights: Activation of 5-HT7 receptors is critical for emotional learning and memory. 5-HT7 receptor-mediated ERK signaling in the amygdala is involved in context- and tone-dependent fear memory. Hippocampal ERK signaling plays a reciprocal role to that in the amygdala in context-dependent fear memory. abstract: Fear conditioning is a valuable behavioral paradigm for studying the neural basis of emotional learning and memory. The present study examined the involvement of extracellular signal-regulated kinase 1/2 (ERK) signaling on the serotonin (5-HT)7 receptor-mediated fear conditioning. Conditioning was performed in a trial in which a tone was followed by an electrical foot-shock. Context- and tone-dependent fear were examined in tests conducted 24 and 48 h after conditioning, respectively. The selective 5-HT7 receptor antagonist 2 a -[4-(4-phenyl-1, 2, 3, 6-tetrahydropyridyl)butyl]-2 a, 3, 4, -tetrahydrobenzo( c, d )indol-2-(1 H )-one (DR4004) (5 mg/kg), when administered intraperitoneally (i.p.) immediately after conditioning, caused a significant decrease in both context- and tone-dependent fear responses (freezing behavior). A significant increase in ERK activity was observed in the amygdala of mice that displayed context- or tone-dependent fear responses, and these changes were also inhibited by the administration of DR4004 (5 mg/kg, i.p.) immediately after conditioning. In contrast, the increase in hippocampal ERK activity in mice that displayed context-dependent fear responses was further enhanced by the administration of DR4004 (5 mg/kg, i.p.). These results suggest that 5-HT7 receptor-mediated ERK signaling may play a significant role in the processes of emotional learning and memory.